ANALISIS RENCANA KEGIATAN DAN ANGGARAN SEKOLAH (RKAS) UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SDN CIPARAY 03 KECAMATAN CIPARAY KABUPATEN BANDUNG - Siti Nuraeni; Turika Masroh, Rika; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational financing management is an essential component in supporting the successful implementation of education in schools. This study aims to analyze educational financing management through the School Activity and Budget Plan (RKAS) at SDN Ciparay 03, Bandung Regency. The study employed a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, documentation, and literature review. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the school's funding sources consist of Performance-Based School Operational Assistance (BOSP Kinerja) amounting to Rp 6,120,000 and budget surplus funds (Silpa) amounting to Rp16,380,000, resulting in a total budget of Rp22,500,000. The budget allocation prioritizes learning process development, curriculum development, learning evaluation, and procurement of administrative facilities. RKAS management is implemented through planning, implementation, monitoring, and evaluation stages based on transparency and accountability principles. The study concludes that educational financing management at SDN Ciparay 03 has been implemented effectively in supporting educational quality improvement, although supervision and evaluation mechanisms still need to be strengthened.